2009
DOI: 10.1002/jso.21274
|View full text |Cite
|
Sign up to set email alerts
|

Debulking surgery for incompletely operated advanced epithelial ovarian carcinoma

Abstract: A history of an incomplete primary surgery does not seem to adversely affect patient prognosis and the optimal cytoreductive success achieved in final debulking surgery is still the most important prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Ovarian cancer (OC) is the most fatal of all gynaecologic malignancies in women. Optimal cytoreductive surgery is the most significant prognostic factor in the management of OC (Harlan et al, 2003;Gultekin et al, 2009). In the event of high index of suspicion for ovarian cancer, patients should undergo surgery in tertiary care units where optimal cytoreductive surgery could be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OC) is the most fatal of all gynaecologic malignancies in women. Optimal cytoreductive surgery is the most significant prognostic factor in the management of OC (Harlan et al, 2003;Gultekin et al, 2009). In the event of high index of suspicion for ovarian cancer, patients should undergo surgery in tertiary care units where optimal cytoreductive surgery could be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Higher complication rate was reported in women who underwent interval cytoreduction compared to upfront completion surgery (26.9 vs. 9.1 %), and the study recommended upfront resurgery over interval cytoreduction when feasible. Gultekin et al reported significantly higher median survival in those patients who underwent upfront completion surgery over those who underwent primary debulking surgery for unexplained reasons (39 vs. 25 months, P = 0.03) [14]. Residual disease was the most important prognostic factor.…”
Section: Discussionmentioning
confidence: 93%
“…6 More recently, for ovarian carcinomatosis, the definition of optimal cytoreductive surgery has evolved, and most authors consider that ''optimal'' should signify macroscopically complete removal of disease, not residual tumor nodules of less than 1-2 cm. 7,8 In conclusion, for carcinomatosis from appendiceal cancer and various origins, the adequate and early therapeutic management combining complete cytoreductive surgery and intraperitoneal chemotherapy will achieve better oncologic outcomes. The negative impact of inadequate previous debulking surgery should be underlined and disseminated to general surgeons and oncologists.…”
mentioning
confidence: 99%